Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1097/meg.0b013e328350fc81
|View full text |Cite
|
Sign up to set email alerts
|

Can oral 5-aminosalicylic acid be administered once daily in the treatment of mild-to-moderate ulcerative colitis? A meta-analysis of randomized-controlled trials

Abstract: The present work showed that oral delayed-release mesalazine administered as a single or a divided dose demonstrated a good safety profile, which was well tolerated and effective as either maintenance or induction treatment. High clinical and/or endoscopic remission rates can be achieved with once-daily dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The benefit of oral 5‐ASA vs. placebo has been demonstrated for mucosal healing (RR = 0.69, 95% CI 0.62–0.77), whatever the frequency of administration (once or multiple times daily), in induction ( P = 0.23) and maintenance ( P = 0.78) . Endoscopic remission rate with combined oral and topical 5‐ASA therapy has not been compared with that seen with monotherapy.…”
Section: ‐Asa Remain the Backbone Therapy For Mild‐to‐moderate Ucmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefit of oral 5‐ASA vs. placebo has been demonstrated for mucosal healing (RR = 0.69, 95% CI 0.62–0.77), whatever the frequency of administration (once or multiple times daily), in induction ( P = 0.23) and maintenance ( P = 0.78) . Endoscopic remission rate with combined oral and topical 5‐ASA therapy has not been compared with that seen with monotherapy.…”
Section: ‐Asa Remain the Backbone Therapy For Mild‐to‐moderate Ucmentioning
confidence: 99%
“…Overall, toxicities related to 5‐ASA are very rare in clinical practice. In RCTs, of 30% of patients who reported AE related to oral 5‐ASA, only 1–2% were severe . The main symptoms associated with oral mesalazine include flatulence, abdominal pain, nausea, diarrhoea and worsening headache.…”
Section: ‐Asa Remain the Backbone Therapy For Mild‐to‐moderate Ucmentioning
confidence: 99%
“…Several previous systematic reviews and meta‐analyses have compared OD with MD dosing of oral mesalamine . To our knowledge, however, no previous meta‐analysis has studied the administration of mesalamine suppositories and the present study is the first to include trials comparing OD with MD suppositories.…”
Section: Discussionmentioning
confidence: 95%
“…Zhu et al . showed that OD dosing can achieve higher remission rates not only for inducing but also for maintaining remission. Tong et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation